Violence in the lives of incarcerated aboriginal mothers in Western Australia - Wilson, Amanda; Jones, J.; Butler, Tony; Simpson, P.; Gilles, M.; Baldry, E.; Levy, M.; Sullivan, E. (Sage Publications, 2017)
© The Author(s) 2017. Drawing on in-depth interviews with incarcerated Aboriginal and Torres Strait Islander mothers in Western Australia, we report on the women’s use of violence in their relationships with others. Results reinforce that Aboriginal women are overwhelmingly victims of violence; however, many women report also using violence, primarily as a strategy to deal with their own high levels of victimization. The “normalization” of violence in their lives and communities places them at high risk of arrest and incarceration. This is compounded by a widespread distrust of the criminal justice system and associated agencies, and a lack of options for community support.